Preoperative Anxiety Levels and the Incidence of Postoperative Nausea and Vomiting in Patients Undergoing General Anesthesia - Widigdo Rekso Negoro; Sindu Sintara; Annes Rindy Permana; Muhammad Rodli; Reko Priyonggo; Suryanto (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Postoperative nausea and vomiting (PONV) are common complications after general anesthesia, negatively impacting patient comfort, recovery, and hospital stay. While many factors contribute to PONV, psychological aspects such as preoperative anxiety are often underestimated despite their influence on postoperative outcomes. This study aimed to analyze the relationship between preoperative anxiety levels and the incidence of PONV in patients undergoing surgery under general anesthesia. Using a cross-sectional design, 45 elective surgical patients were assessed for anxiety using the Hamilton Anxiety Rating Scale (HARS), and PONV incidence was recorded within 24 hours post-surgery. Chi-square analysis revealed a significant association between anxiety levels and PONV occurrence (p = 0.002). Among patients with moderate to severe anxiety, 73.3% experienced PONV, compared to only 26.7% among those with mild anxiety. These findings indicate that higher preoperative anxiety increases the risk of PONV. Therefore, integrating psychological assessment and anxiety management into perioperative care is crucial to reducing postoperative complications and improving anesthetic outcomes through a more holistic patient care approach.